The Importance of Using Literature in Foreign Language Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this paper, importance of using literary sources in a foreign language classes is investigated and highlightedstudy is an attempt to investigate and highlight the significance of using appropriate carefully selected literary materials in FL/SL Classrooms.Literature is considered an important and useful means of teaching foreign languages. In the process of using literature, four basic language skills like reading, writing, listening and speaking must be taught in integrated way. Both oral and written communication must be taught with the sources which includes basic language skills as an integral a part language use, as a part of the means for creating both referential and interactional meaning, not merely as a facet of the oral and written production of words, phrases and sentences.